ANALISIS PENERAPAN MODEL PROJECT BASED LEARNING (PJBL) PADA PEMBELAJARAN BIOLOGI DI SMA NEGERI 10 MEDAN - Sapna Marsyalina Br Barus, Emia; Dwita Syahfitri, Intan; Putri, Nadilla; Safitri, Yunda; Arwita, Widya; Mukra, Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Project Based Learning (PjBL) model in biology learning at SMA Negeri 10 Medan. The background of this study is based on the low level of student engagement in teacher-centered learning, which results in less optimal learning activities. This study uses a descriptive qualitative approach with a biology teacher as the research subject. Data were collected through interviews, indirect observation, and documentation. The results show that the implementation of Project Based Learning is able to increase student activeness in the learning process, especially in discussions, group work, and project presentations. Students also show higher enthusiasm as they are directly involved in contextual and experience-based learning activities. In addition, this model encourages students to be more independent in seeking information and actively construct their own knowledge. However, several challenges were found in its implementation, such as unequal participation in group work and limited learning facilities and media. Despite these obstacles, the implementation of Project Based Learning still has a positive impact in creating a more interactive, collaborative, and student-centered learning environment. Therefore, this model can be considered an effective alternative in improving the quality of the biology learning process.